Social Networks, Socioemotional Development and Social Isolation in Adolescents: A Systematic Review - Ordóñez Jiménez, María Auxiliadora (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
The COVID-19 pandemic has had a great impact on the emotional and social development of adolescents, with social networks constituting an essential tool for constructing their identity. The aim of this article is to conduct a systematic review focusing on the impact of social networks on the socioemotional development of adolescents, paying special attention to feelings of social isolation. The results highlight the role of social networks as tools to nurture feelings of belonging. As main conclusions, the importance of promoting a good use of social networks as a space for emotional growth is mentioned.